Inter-subject Variability of LTD-like Plasticity in Human Motor Cortex: A Matter of Preceding Motor Activation - Goldsworthy, Mitchell R.; Müller-Dahlhaus, Florian; Ridding, Michael C.; Ziemann, Ulf (Brain stimulation, 2014)
Continuous theta burst stimulation (cTBS) of the human primary motor cortex (M1) induces long-term depression (LTD)-like plastic changes in corticospinal excitability, but several studies have reported high inter-subject variability of this effect. Most studies use a tonic voluntary contraction of the target muscle before cTBS to set stimulation intensity; however, it is unclear how this might affect response variability. To examine the influence of pre-activation of the target hand muscle on inter-subject response variability to cTBS of the human M1. The response to cTBS was assessed by changes in motor evoked potential (MEP) amplitude in the right first dorsal interosseous (FDI) muscle. For Study 1, ten healthy subjects attended two sessions. They were instructed in one session to keep their FDI relaxed for the entire testing period (pre-relax), and in the other to perform a 2-min 10% of maximal voluntary tonic contraction 15 min before cTBS (pre-active). For Study 2, data from our previous study were re-analyzed to extend the pre-relax condition to an additional 26 subjects (total n = 36). cTBS-induced highly consistent LTD-like MEP depression in the pre-relax condition, but not in the pre-active condition. Inter-subject response variability increased in the pre-active condition. cTBS induces consistent LTD-like plasticity with low inter-subject variability if pre-activation of the stimulated motor cortex is avoided. This affirms a translational potential of cTBS in clinical applications that aim at reducing cortical excitability.